Prevalence and incidence of kidney diseases leading to hospital admission in people living with HIV in France: an observational nationwide study. Issue 5 (5th May 2019) - Louis, Magali; Cottenet, Jonathan; Salmon-Rousseau, Arnaud; Blot, Mathieu; Bonnot, Pierre-Henri; Rebibou, Jean-Michel; Chavanet, Pascal; Mousson, Christiane; Quantin, Catherine; Piroth, Lionel
Abstract : Objectives: To describe hospitalisations for kidney disease (KD) among people living with HIV (PLHIV) in France and to identify the factors associated with such hospitalisations since data on the epidemiology of KD leading to hospitalisation are globally scarce. Design: Observational nationwide study using the French Programme de Médicalisation des Systèmes d'Information database. Setting: France 2008–2013. Participants: Around 10 862 PLHIV out of a mean of 5 210 856 patients hospitalised each year. All hospital admissions with a main diagnosis code indicating KD (International Classification of Diseases, 10th revision codes, N00 to –N39) were collected. Main outcome measures: The prevalence and incidence of KD leading to hospital admission in PLHIV and the associated risk factors. Results: The prevalence of patients hospitalised for KD was 1.5 higher in PLHIV than in the general population, and increased significantly from 3.0% in 2008 to 3.7% in 2013 (p<0.01). The main cause of hospitalisation for KD was acute renal failure (ARF, 25.4%). Glomerular diseases remained stable (6.4%) throughout the study period, focal segmental glomerulosclerosis being the main diagnosis (37.6%). Only 41.3% of patients hospitalised for glomerular disease were biopsied. The other common motives for admission were nephrolithiasis (22.1%) and pyelonephritis (22.6%). The 5-year cumulative incidence of KD requiring hospitalisation was 5.9% in HIV patients newly diagnosed for HIV in 2009. Factors associated with a higher risk of incident KD requiring hospitalisation were cardiovascular disease (HR 3.30, 95% CI 1.46 to 7.49), and, for female patients, AIDS (HR 2.45, 95% CI 1.07 to 5.58). Two-thirds of hospitalisations for incident ARF occurred in the first 2 years of follow-up. Conclusions: Hospital admission for KD is more frequent in PLHIV than in the general population and increases over time. ARF remains the leading cause. Glomerular diseases are infrequently documented by renal biopsies. Older patients and those with cardiovascular disease are particularly concerned.